2018
DOI: 10.1002/jcla.22616
|View full text |Cite
|
Sign up to set email alerts
|

A promising, novel index in the diagnosis and follow‐up of patent ductus arteriosus: Red cell distribution width‐to‐platelet ratio

Abstract: Red cell distribution width-to-platelet ratio and PCT may be promising supportive tools for the diagnosis and prediction of pharmacotherapy success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
1
22
2
1
Order By: Relevance
“…However, no correlation was detected between thrombocytopenia and hsPDA in numerous other studies. 12,17,28 In our study, we did not observe a correlation between hsPDA and platelet count or thrombocytopenia in the first hours of life. Moreover, we showed that platelet count was not associated with outcomes of pharmacological treatment of hsPDA, corroborating other reports.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…However, no correlation was detected between thrombocytopenia and hsPDA in numerous other studies. 12,17,28 In our study, we did not observe a correlation between hsPDA and platelet count or thrombocytopenia in the first hours of life. Moreover, we showed that platelet count was not associated with outcomes of pharmacological treatment of hsPDA, corroborating other reports.…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, we showed that platelet count was not associated with outcomes of pharmacological treatment of hsPDA, corroborating other reports. 3,[11][12][13][14][15]29 Discrepancies in the results of these various studies may be attributed to differences in neonatal thrombocytopenia and hsPDA definitions, gestational ages of the studied infants, exclusion criteria, timing of platelet count, and comorbidities, as well as the retrospective nature of most of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are limited studies on the use of RDW in neonates for monitoring patients and determining their prognosis. It has been reported that the increase in RDW in preterm infants may be associated with patent ductus arteriosus, bronchopulmonary dysplasia, and LOS . A high RDW value has been shown to reflect unstable erythropoiesis and inflammatory stress in critically ill neonates .…”
Section: Discussionmentioning
confidence: 99%